Analisis Penilaian Persediaan Barang Dagang Pada Rozan Mini Market & Percetakan Sesuai Sak Etap - Tommy Kuncara; Fera Riske Anggita; Jessica Livia Utomo (Politeknik Ganesha Medan, 2023)
Inventory is one of the current assets that must be managed properly, especially for companies that have merchandise inventory. The purpose of this study was to determine the application of methods based on and assessment of goods according to ETAP CHAPTER 11 which are suitable for Rozan Mini Market & Printing. The data analysis technique with the inventory system used is the Perpetual System and the Inventory Method used is the FIFO Method and the Average Method. The types and sources of data used are primary data and secondary data. The conclusion obtained from the research that has been carried out is that Rozan Mini Market & printing in recording inventory has not yet Financial Accounting Standards for Public Accountability Entities (SAK ETAP) CHAPTER 11 and the application of Rozan Mini Market & printing applies a perpetual system, and the method used is the FIFO method, because the HPP according to the FIFO method tends to be smaller than the Average method